Integrated Care for Older People Screening Tool for Measuring Intrinsic Capacity: Preliminary Findings From ICOPE Pilot in China - Ma, Lina; Chhetri, Jagadish K.; Zhang, Yaxin; Liu, Pan; Chen, Yumeng; Li, Yun; Chan, Piu (Frontiers in Medicine, 2020)
Objectives: The World Health Organization (WHO) proposed the Integrated Care for Older People (ICOPE) screening tool to identify older people with priority conditions associated with declines in intrinsic capacity (IC). We aimed to determine the clinical utility of the WHO ICOPE screening tool in a Chinese population. Method: A total of 376 adults aged 68.65 ± 11.41 years participated in the study. IC was assessed with the WHO ICOPE screening tool, covering five domains: cognitive, locomotor, sensory, vision, and psychological capacity. We assessed the activities of daily living (ADL), instrumental activities of daily living (IADL), the Fried frailty phenotype, FRAIL scale, SARC-F scale, Mini-mental State Examination (MMSE), Geriatric Depression Scale (GDS), social frailty, and quality of life. Results: There were 260 (69.1%) participants who showed declines in one or more IC dimensions. The percentages of decline in mobility, cognition, vitality, hearing, vision, and psychological capacity were 25.3%, 46.8%, 16.2%, 15.4%, 11.7%, and 12.0%, respectively. IC decreased with increasing age. After adjusting for age, sex, and multimorbidity, participants with declines in IC were more likely to be older, frail, and disabled. They also had worse physical, mental, and overall health. There was a higher prevalence of declines in IC in participants with frailty. After adjusting for age, IC was positively correlated with walking speed, resilience score, and MMSE score and negatively correlated with frailty, SARC-F score, IADL score, GDS score, and physical and mental fatigue. The IC score was not associated with body composition variables such as fat-free mass, body fat percentage, or visceral fat area. Higher IC was associated with better quality of life. The AUC-ROC for the ICOPE screening tool versus Fried phenotype, FRAIL, ADL disability, IADL disability and SARC-F were 0.817, 0.843, 0.954, 0.912, and 0.909, respectively. Conclusion: Our research affirms that the ICOPE screening tool is useful to identify adults with poor physical and mental function in a Chinese sample. This tool may assist in identifying declines in IC in an integrative care model and help slow down function decline and onset of care dependence.